GOVERNMENT RESPONSE TO CASSAVA TRADE GOVERNANCE IN LAMPUNG: FROM PRICE CRISIS TO POLICY ORCHESTRATION - Darmawan Purba; Feni Rosalia; Arizka Warganegara (Adisam Publisher, 2026)
This study examines the development of cassava trade governance in Lampung Province through a narrative policy analysis of 76 online news reports published between 2014 and 2026. The analysis compares four gubernatorial periods: M. Ridho Ficardo, Arinal Djunaidi, Acting Governor Samsudin, and Rahmat Mirzani Djausal. The findings show a gradual shift from market-based governance, initial government coordination, crisis mobilisation, to more formalised policy orchestration. In the earlier periods, cassava governance was mainly shaped by farmers, collectors, and processing factories, while government intervention remained limited. The 2024 price decline expanded the issue into a wider public-governance crisis. Under Rahmat Mirzani Djausal, the provincial government began to formalise its response through gubernatorial instruction and regulation on price arrangements, deduction practices, governance, and downstreaming. The study argues that strategic commodity governance requires actor coordination, institutional rules, and sustained government facilitation.